Molecular mechanisms of avian immunoglobulin gene diversification and prospect for industrial applications - Seo, Hidetaka; Hirota, Kouji; Ohta, Kunihiro (Frontiers in Immunology, 2024)
Poultry immunoglobulin genes undergo diversification through homologous recombination (HR) and somatic hypermutation (SHM). Most animals share a similar system in immunoglobulin diversification, with the rare exception that human and murine immunoglobulin genes diversify through V(D)J recombination. Poultry possesses only one functional variable gene for each immunoglobulin heavy (HC) and light chains (LC), with clusters of non-productive pseudogenes upstream. During the B cell development, the functional variable gene is overwritten by sequences from the pseudo-variable genes via a process known as gene conversion (GC), a kind of HR. Point mutations caused in the functional variable gene also contribute to immunoglobulin diversification. This review discusses the latest findings on the molecular mechanisms of antibody gene diversification in poultry, using chickens as a model. Additionally, it will outline how these basic research findings have recently been applied especially in the medical field.